2019
DOI: 10.5114/pjp.2019.90393
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of mixed epithelial/mesenchymal metaplastic breast carcinoma (carcinosarcoma): a meta-analysis of Chinese patients

Abstract: Breast carcinosarcoma is a rare and aggressive subtype of metaplastic breast cancer. Data focusing on breast carcinosarcoma is limited. The purposes of this study are to describe the clinicopathological features of breast carcinosarcoma and to evaluate post-surgical outcomes. Material and methods: All case reports about breast carcinosarcoma in China were collected from eligible papers published in Chinese core periodicals between 1990 and 2015 with key words of breast carcinosarcoma, breast cancer, carcinosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…[4][5][6] The pathological features of MBC are usually triple negative. [7][8][9] In this case, the breast tumor was large but painless and the pathological features were consistent with those reported in the literature.…”
Section: Discussion and Reviewsupporting
confidence: 89%
See 1 more Smart Citation
“…[4][5][6] The pathological features of MBC are usually triple negative. [7][8][9] In this case, the breast tumor was large but painless and the pathological features were consistent with those reported in the literature.…”
Section: Discussion and Reviewsupporting
confidence: 89%
“…Moreover, MBC has low sensitivity to chemotherapy. Although anthracyclines have been recommended to treat this special cancer in a previous study, [9] there is still no standard systematic treatment for MBC. In this case, there was no change in the breast lump after 3 cycles of epirubicin and cyclophosphamide chemotherapy (epirubicin + cyclophosphamide), which may be partly due to the heterogeneity of the patient’s tumor.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Also, as lymph node involvement is less likely, most patients underwent surgical options upfront and received less chemotherapy or radiotherapy than other TNBCs. One meta-analysis confirmed that adjuvant treatment after surgical management may improve 5-year OS in patients with MPC [26]. Our study also shows that NAT did not add to the OS benefit in the node-positive subset.…”
Section: Discussionsupporting
confidence: 50%
“…The five-year survival rate in patients with breast carcinoma is 56.7 % with a median survival time of 71 months [ 10 ]. In the invasive ductal carcinoma subtype with metastasis to the liver, orbit, and bones, as noted in the present study, the chances of survival are low.…”
Section: Discussionmentioning
confidence: 99%